Liquid nitrogen for the treatment of actinic keratosis: A longitudinal assessment - Ianhez, Mayra; Miot, Hélio Amante [UNESP]; Bagatin, Edileia (Elsevier B.V., 2014)
Cryosurgery with liquid nitrogen is one of the most used treatments for actinic keratosis. We aimed to study the effectiveness of two consecutive sessions of cryosurgery for actinic keratosis and investigate factors associated with its therapeutic success. Hence, we conducted a longitudinal study including 92 patients of both sexes, aged 50-75 years with 5-50 actinic keratosis on the face and forearms, who underwent cryosurgery and treatment with sunscreen SPF 30, at baseline and after 120 days. The lesions were counted in duplicate by the same examiner before the start of treatment and after 120 (N = 92) and 300 days (N = 33), represented by their medians and quartiles and compared using the generalized linear mixed effects model (negative binomial). Treatment behavior was investigated in relation to sex, age, education, skin type, smoking, sun exposure at work and the use of aspirin, anti-inflammatory and angiotensin-converting enzyme inhibitors. There was a significant reduction in the actinic keratosis count on the face and forearms (p < 0.05). Our results confirmed the effectiveness of cryosurgery for actinic keratosis, with a 57% reduction in the number, and size of the lesions. Higher education levels (p = 0.02) and less sun exposure at work (p = 0.02) independently promoted a significant reduction in the actinic keratosis count. Different population groups showed characteristic responses to the treatment, which may be explained by the degree of adherence to the use of photoprotection. In two sessions, cryosurgery with liquid nitrogen reduced the actinic keratosis count. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Cryosurgery; Actinic keratosis; Carcinogenesis; Prevention and control; Skin neoplasm; Treatment outcome